Molecular methods for the specific detection of Colletotrichum sansevieriae - Sandoval-Ruiz, Rebeca (2025)
Introduction. Sansevieria anthracnose, caused by Colletotrichum sansevieriae, represents a significant risk to the cultivation and export of this ornamental plant. Effective and rapid identification methods for this pathogen are crucial for implementing control measures to prevent its spread to uninfected areas. Objective. To implement and optimize molecular methods for the rapid and reliable identification of C. sansevieriae. Materials and methods. During 2016, a β-tubulin-2 (β-tub2) gene fragment of C. sansevieriae isolated from a local farm in Alajuela, Costa Rica, was analyzed. PCR-RFLP of the partial β-tubulin-2 (β-tub2) gene fragment was implemented using the enzyme MseI (Tru1I). In addition, species-specific primers for C. sansevieriae detection and PCR-RFLP analysis of the amplified fragment were applied. Results. The digestion consistently produced a two-band restriction pattern specific to C. sansevieriae. The designed primers successfully amplified a 383 bp fragment of the β-tub2 from all C. sansevieriae strains tested. No amplification was observed from other Colletotrichum species within the C. gloeosporioides and C. acutatum complexes, as well as from C. truncatum and Fusarium oxysporum isolates. Moreover, this restriction site, located within the amplicon generated by the species-specific primers for C. sansevieriae, enabled successful validation of the species through digestion. Conclusions. Both PCR based methods demonstrated sufficient sensitivity to detect C. sansevieriae in naturally and artificially infected Sansevieria leaves without the need to isolate the pathogen in pure cultures, making the diagnostic process more efficient and accessible.